Pengembangan Model Sistem Informasi Akuntansi Manajemen Untuk Pengendalian Kualitas Produk Pada PT. Lucky Textile Semarang II Di Semarang - Yunitria Mawadah; Muchayatin Muchayatin (FEB UNTAG Semarang, 2018)
This study aims to determine the application, constraints, and development of accounting management information system model for product quality control at PT. Lucky Textile Semarang II in semarang. The data were collect by direct observation, documentation, and literatur. This research used descriptive qualitative method with technique of triangulation analysis and 5 step of accounting management information system.The results showed that the existence of accounting management information systems for product quality control support the production, quality control, quality assurance, and production control in running each activity on their section in to produce the products that suitable with quality standards. Development of accounting management information system for product quality control should be added accountability report for defective product and downtime report (waiting time handling defect product). The use of accounting management information systems, can not be separated from the risks that exist such as input errors by users system, invalid information, and errors in software and hardware used.